Analisis Variasi Suhu Terhadap Variasi Cahaya Pada Rancang Bangun Solar Test Simulator Menggunakan Peltier - ., Cholish; Rusdi, Muhammad; Rahmawaty, Rahmawaty; Pulungan, M Anhar; Azis, Abdul; abdullah, abdullah; Irawan, Shahril; Othman, Zulkifli (Rekayasa Material, Manufaktur dan Energi, 2024)
The implementation of the Solar Panel Test Simulator design is carried out for testing in accordance with environmental temperature conditions. The difficulty of carrying out tests in actual conditions is the background for designing this tool. The intensity of heat from sunlight and also the variable ambient temperature influence the voltage released by solar panels. To obtain a solar panel voltage measurement data sheet like the situation above, it is necessary to design a simulation tool that is capable of being a reference to the actual situation. Peltier is useful for controlling temperature variations ranging from normal temperatures to below normal temperatures. Peltier is able to maintain temperature conditions until it is stable at 32 degrees Celsius by receiving light intensity. For light variations, researchers use halogen lamps which will function as heat providers. Solar light is capable of providing lighting intensity ranging from 0 - 100%. However, in this test we only use 3 conditions, namely light intensity of 30%, 60% and 100%. This test also aims to determine the effect of the voltage produced by solar panels on changes in light and also to determine the effect of the voltage produced by solar panels on changes in temperature and to determine the effect of changes in temperature on changes in light intensity. This tool is expected to be able to provide test results that can be used as a reference in measuring solar panels in real conditions.